Localized and historical hypermobile spectrum disorders share self-reported symptoms and comorbidities with hEDS and HSD - Fairweather, DeLisa; Bruno, Katelyn A.; Darakjian, Ashley A.; Wilson, Frances C.; Fliess, Jessica J.; Murphy, Emma F.; Kocsis, S. Christian; Strandes, Max W.; Weigel, Gabriel J.; Puls, Alayna M.; Hartmoyer, Cameron J.; Hamilton, Charwan; et al. (Frontiers in Medicine, 2025)
BackgroundIn 2017 a revised clinical criterion for the diagnosis of hypermobile Ehlers-Danlos syndrome (hEDS) was proposed in order to better distinguish hEDS from other joint hypermobility disorders which are termed hypermobility spectrum disorders (HSD). The goal of this study was to determine whether patients with localized HSD (L-HSD) or historical HSD (H-HSD) differed in 100 symptoms/comorbidities from controls and/or patients diagnosed with hEDS or HSD.MethodsIn this study, we examined 100 self-reported symptoms/comorbidities from 2,695 patients diagnosed with hEDS, HSD, L-HSD/H-HSD, or controls.ResultsFrom November 1, 2019, to August 27, 2024, 2,695 patients filled out an Intake Questionnaire at the Mayo Clinic Florida EDS Clinic. Using the 2017 diagnostic criterion, 60.6% (n = 1,632) of patients were diagnosed with HSD, 18.3% (n = 493) hEDS, 10.7% (n = 289) with L-HSD or H-HSD, and 10.4% (n = 281) were controls without any of these diagnoses. We found that patients with L-HSD/H-HSD self-reported significantly more symptoms/comorbidities than controls for 62/100 (62%) of issues compared to 58/100 (58%) for HSD and 20/100 (20%) for hEDS. These findings suggest that L-HSD/H-HSD share similar symptoms and comorbidities to HSD. Interestingly, patients with L-HSD/H-HSD self-reported significantly more symptoms/comorbidities than patients diagnosed with hEDS or HSD for 20/100 (20%) of issues such as joint pain, muscle weakness, multiple sensitivities, wheezing/shortness of breath, gastroesophageal reflux disease (GERD), pain/cramps in the lower abdomen, constipation, heat and/or cold intolerance, hearing difficulties, attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), snoring, and narcolepsy. Symptoms/comorbidities that were significantly increased in L-HSD/H-HSD patients compared to controls (but not in hEDS or HSD compared to controls) and so were specific to this diagnosis included wheezing, hearing difficulties, narcolepsy, circadian rhythm disorders, and ASD.ConclusionWe found that patients with L-HSD/H-HSD had many symptoms and comorbidities that closely resembled HSD suggesting that revised diagnostic criteria for hEDS and HSD should include L-HSD/H-HSD within a diagnosis of HSD. Additionally, our data further suggest that patients with HSD (including L-HSD/H-HSD) have more symptoms/comorbidities than patients with hEDS.